Clinical features, management, and prognosis of chronic limb-threatening ischemia - Koivunen, Veerakaisa (fi=Turun yliopisto|en=University of Turku|, 2022)
Lower extremity artery disease (LEAD) associates with amputations, mortality, and systemic atherosclerosis. The most extensive and severe form of LEAD, chronic limb-threatening ischemia (CLTI), associates with the highest rates of adverse events. CLTI is poorly understood due to its heterogenous nature and unpredictable progression. It is thus substantially underdiagnosed and undertreated. This thesis aimed to investigate in depth the clinical features, treatment, and prognosis of CLTI in patients. The findings indicate that CLTI is an extensive arterial multi-site disease with severe crural involvement with typical associated risk factor profile. Ascertaining the patients with the highest risk of adverse events is challenging and current models have only modest predictive abilities. The information about distal atherosclerosis, the sex of patient, toe-brachial index (TBI) and toe pressure (TP) measurements could enhance the estimation. Despite the predominant location of atherosclerosis, TBI and TP are predictive of mortality. TBI and TP overcome the common problem of medial sclerosis and incompressible ankle arteries and therefore, they should be assessed together with ankle-brachial index (ABI). A surgical revascularization, if possible, should be chosen as it associates with better outcomes compared to an endovascular intervention. However, not all patients can be surgically revascularized; thus, endovascular revascularization or primary amputation may be the most appropriate treatment option in the long-term for such patients. Senescence and diabetes mellitus are becoming more frequent as the main risk factors of LEAD, therefore a proportionate increase could be expected to occur for the number of CLTI patients and for the need of vascular care. This thesis demonstrates that clinical decision making is challenging in the treatment planning of CLTI. Risk factor modification, diagnostics, prognosis, and revascularizations are tools to combat the growing health burden of CLTI. However, amputation remains as the only realistic treatment for a significant proportion of CLTI patients.